Collaborative care model versus usual care for people with musculoskeletal conditions and co-existing anxiety and depression: protocol for a feasibility mixed-methods randomised controlled trial - Maria Joao Cardoso Teixeira; Rokhsaneh Tehrany; Anju Jaggi; Refah Ahmed; Lucy Dove; Parashar Ramanuj (BJPsych Open, 2023)
Background In the UK 17.8 million people have musculoskeletal pathophysiology, which becomes universal with age. Levels of discomfort and incapability correlate with symptoms of anxiety and depression. People with sufficient symptoms who seek care can benefit from collaborative diagnosis and treatment of mental and physical health organised by a case manager. This paper presents the protocol for a feasibility trial of collaborative care in an orthopaedic setting.